THE DIFFERENCES OF STUDENTS’ LEARNING ACHIEVEMENT BY POSTER DISPLAYING ON ENVIRONMENT TOPIC GRADE X SMA OF MEDAN - Febrina Suci Ramadhoni; Martina Asiati Napitupulu (Universitas Negeri Medan, 2016)
The study aims to know the difference of learning achievement by poster displaying in the environmental topic. Type of the research was quasi experiment and was designed with pre-test and post-test. The population is the students in SMA Negeri 3 and 4 Medan academic year 2015/2016. The samples consists of two groups selected purpousively for each of school, grade X MIA 10 as poster making inclution group (n=40 students) and X MIA 7 as poster non-making inclution group (n=40 students). Learning method in both groups was goup discussion. In first group, used poster making inclution and poster non-making inclution for the second. Multiple choice test was the instrument for cognitive data collection and questionnaires were used for student performances. Hypothesis wass tested by t-test. The students learning achievement result showed that, the average score in poster making inclution group (74.92) was higher than poster non-making inclution group (67.13) with persentage difference is 38%. tcount with ttable is tcount > ttable ( 4.175 > 1.994) (with α=0.05 and df=78). Based on the data from research result used tcount > ttable then H0 was rejected and Ha was accepted. It means there is difference of learning achievement between student who were treated with poster making inclution and those treated with non-poster making inclution model on Environmental topic of Grade X in SMA at Medan Academic Year 2015/2016. Keywords: Poster Making Inclution Group,Poster Non-Making Inclution Group Learning Achievement, Student Performance